P029 Lifetime cancer risk in the british rubber industry. a retrospective cohort with 45 year follow-up. (1st September 2016) - Hidajat, Mira; McElvenny, Damien; MacCalman, Laura; Alexander, Carla; Cherrie, John; Darnton, Andrew; Agius, Raymond; Vocht, Frank de
Abstract : There exists a great deal of uncertainty as to which specific chemicals present in the rubber products manufacturing industry give rise to the increases in cancer that have been seen to date and which are regarded by the International Agency for Research on Cancer (IARC) as carcinogenic; especially since after this IARC classification, exposures in the rubber industry have decreased considerably and efforts have been made to remove confirmed carcinogens from the production process. We updated a cohort of 40, 867 men who were employed in the British rubber industry on 1 February 1967. Follow-up was last updated until 1976 and an excess risk of bladder cancer in men likely exposure to beta-naphthylamine based antioxidants (before these were withdrawn from the process in 1949), excess death from lung cancer across the industry and excess mortality from stomach cancer in the tyre sector were observed. We have extended the mortality follow-up to 45-years and are linking it to a population-specific quantitative job-exposure matrix based on available data previously collected in the EU EXASRUB project. We are currently waiting for tracing outcomes for mortality by the Health & Social Care Information Centre (HSCIC), and so we will present the first results of industry- and job-specific cancer mortality risks as well as quantitative exposure-response associations for rubber dust and fumes and specific n-Nitrosamines. There are only few occupational cohorts of this size with such long follow-up, so the presented analyses will provide an important overview of lifetime exposure-specific cancer mortality risks of specific exposures historically and currently encountered in the industry.